PREOPERTIVE STAGING OF RECTAL CARNCER WITH MRI - Ana Lazarova; Aleksandar Karagjozov (Medical faculty, Ss Cyril and Methodius University Skopje, 2018)
Introduction: Rectal cancer is the third most common malignant disease worldwide with a high mortality rate in developed countries .. The magnetic resonance imaging method p lays a crucial role in the pre-operational staging of the rectal cancer. MR is a modality of choice for rectal cancer staging, which assists the surgeon in achieving negative resection margins. In fact, MR assists the surgeon in the planning of the type of surgical treatment, and also helps to predict the response to treatment and disease detection. Material and Methods: 61 patients '\lith c'olonoscopy proven rectal cancer have been treated treated with pre-ope_rative 1.5 T MRI of small pelvis in standard planes and pulse sequences (SAG T2, AX Ti, T2, DWI, COR STIR) Results: A tabular presentation of the results is given witch conelated the preoperative MR T staging with the pathohistological finding. The comparison was made in Tl, T2, T3 and T4 MR stadium with the acquired pathohistological stadium. The second table showing a percentage view of the difference between MR preoperative stadium and pathohistological results. Also a tabular presentation with general infom1ation for patients is given ; gender , nationality and age. Conclusion: MR as an ideal imaging method for preoperative staging for a local or advanced stage of rectal cancer. MR allows evaluation of extramural spreading, determines the mesorectal involvement and involves the margin of resection.
Keywords: rectal carcinoma; MR. preoperative staging; pathohistological findings.